Peran Pesantren dalam Mencegah Gerakan Radikalisme di Kalimantan Barat - Syaiful Ilmi; Ardiansyah Ardiansyah (Cakrawala: Jurnal Studi Islam, 2020)
Islamic boarding schools are naturally known as reputable Islamic educational institutions that consistently breeds inclusive and tolerant values. However, radicalism in the name of religion has become increasingly common in Indonesia. This study aims to analyze the strategy used by the Islamic boarding schools in West Borneo in countering the radicalism movement with the AGIL paradigm. This study uses the phenomenological approach and considered four objects, which are: Darul Khairat Islamic Boarding School, Makarim al-Akhlaq Islamic Boarding School, Darul Ulum Islamic Boarding School and Darussalam Islamic Boarding School. The results reveal that Islamic boarding schools apply the following strategies which are: internalizing Sufistic teachings, applying salaf education, instilling the Ahlu Sunnah wa al Jama'ah doctrine, and instilling the values of tolerance and pluralist attitudes.